A comprehensive energy efficiency study of segmented annular thermoelectric generator; thermal, exergetic and economic analysis. (25th November 2020) - Tian, Man-Wen; Mihardjo, Leonardus W.W.; Moria, Hazim; Asaadi, Soheil; Sadighi Dizaji, Hamed; Khalilarya, Shahram; Nguyen, Phong Thanh
Graphical abstract: Highlight: Segmented annular thermoelectric was compared with non-segmented. Geometries of the segmented thermoelectric were investigated. Energy, exergy and economic criterions were evaluated. The method of two-stage was compared with segmenting method. Abstract: Annular thermoelectric generator (ATEG) has not been commercialized yet and many studies are required to identify its characteristics from different viewpoints. Most recently, segmented annular thermoelectric was proposed as an efficient structure for annular thermoelectric in which each leg of thermoelectric (n-type and p-type) is made of two different materials termed low temperature material and high temperature material. Although a few of investigations have reported thermal behavior of segmented annular thermoelectric, no exergetic and economic analysis have been performed yet on segmented annular thermoelectric generators. Exergetic and economic evaluations are significant criteria on marketing area of any industrial product. Hence, in this study, a comparison between segmented and non-segmented annular thermoelectric is first presented and then the impacts of the main parameters of segmented annular thermoelectric generator on energy, exergy and economic factors (including output power, conversion efficiency, exergy efficiency and cost per unit of output power) are comprehensively investigated and presented via validated 3-D numerical simulation method. The results showed that the segmented thermoelectric is more efficient than the non-segmented thermoelectric from the viewpoint of all said criteria. A peak point was observed for the curve behavior of most geometric characteristics of the segmented annular thermoelectric generator which is remarkable and discussed in this paper.